Endocrine manifestations related to inherited metabolic diseases in adults - Vantyghem, Marie-Christine (BioMed Central, 2012)
Most inborn errors of metabolism (IEM) are recessive, genetically transmitted diseases and are classified into 3 main groups according to their mechanisms: cellular intoxication, energy deficiency, and defects of complex molecules. They can be associated with endocrine manifestations, which may be complications from a previously diagnosed IEM of childhood onset. More rarely, endocrinopathies can signal an IEM in adulthood, which should be suspected when an endocrine disorder is associated with multisystemic involvement (neurological, muscular, hepatic features, etc.). IEM can affect all glands, but diabetes mellitus, thyroid dysfunction and hypogonadism are the most frequent disorders. A single IEM can present with multiple endocrine dysfunctions, especially those involving energy deficiency (respiratory chain defects), and metal (hemochromatosis) and storage disorders (cystinosis). Non-autoimmune diabetes mellitus, thyroid dysfunction and/or goiter and sometimes hypoparathyroidism should steer the diagnosis towards a respiratory chain defect. Hypogonadotropic hypogonadism is frequent in haemochromatosis (often associated with diabetes), whereas primary hypogonadism is reported in Alström disease and cystinosis (both associated with diabetes, the latter also with thyroid dysfunction) and galactosemia. Hypogonadism is also frequent in X-linked adrenoleukodystrophy (with adrenal failure), congenital disorders of glycosylation, and Fabry and glycogen storage diseases (along with thyroid dysfunction in the first 3 and diabetes in the last). This is a new and growing field and is not yet very well recognized in adulthood despite its consequences on growth, bone metabolism and fertility. For this reason, physicians managing adult patients should be aware of these diagnoses.